Leadership in transformation between local embeddedness and global challenges - Johannes Steyrer; Ronald Hartz; Michael Schiffinger (Journal for East European Management Studies, 2006)
Based on empirical studies in Romania, Estonia, Germany, and Austria within the GLOBE project, the authors try to answer the question of cultural embeddedness of leadership patterns in an environment of more and more globalised management. Special emphasis is put on the match/mismatch of the observed styles of leadership behaviour of CEO`s with regional and global expectations, on the differences and similarities between the examined countries, the influence of transformational settings in the CEE countries, and the prospective changes due to a new generation of managers. – – Auf der Basis empirischer Studien in Rumänien, Estland, Deutschland und Österreich im Rahmen des GLOBE - Projektes, gehen die Autoren der Frage nach der kulturellen Einbindung von Führungsmustern unter Bedingungen eines zunehmend globalisierten Managements nach. Im Zentrum stehen dabei der Vergleich der beobachteten Führungsstilmuster von Geschäftsführern mit den regionalen und globalen Erwartungen der Nachgeordneten, die Unterschiede und Ähnlichkeiten zwischen den untersuchten Ländern, der Einfluss der Transformationsbedingungen in den MOE-Staaten sowie die erwarteten Veränderungen durch einen Generationswechsel im Management.
Keywords: 650; leadership; transformation; GLOBE; cultural embeddedness; CEE countries